Intergenerational transmission of poverty and inequality: young lives - Behrman, J; Schott, W; Mani, S; Crookston, B; Dearden, K; Duc, L; Fernald, L; Stein, A; Young Lives Determinants and Consequences of Child Growth Project Team (Young Lives, 2013)
There is considerable emphasis in academic and policy literatures on intergenerational transmissions of poverty and inequality. The perception is that improving schooling attainment and income/consumption for parents in poor households will result in important reductions in poverty and inequality for the next generation of adults. However, the extents of these intergenerational effects on poverty and inequality are empirical questions that have not been examined much if at all, particularly for developing countries. We use data on children born in the 21st century in four developing countries to estimate critical relations with which to simulate how changes in parents’ schooling attainment and consumption would affect poverty headcounts and inequality in the children’s generation when the children become adults. We find that reductions in poverty headcounts and inequalities in the parents’ generation carry over to distributions of human capital and per capita adult consumption for the children’s generation, but the effects are not very large for the distribution of per capita consumption. Therefore, while reductions in poverty and inequality in the parents’ generation are likely to be desirable in themselves to improve welfare among current adults, they are not likely to have much impact on reducing per capita consumption poverty and inequality in the next generation of adults.